Ontología del cuerpo y estética de la enfermedad en Jean-Luc Nancy: De la téchne de los cuerpos a laapostasía de los órganos - Vásquez Rocca, Adolfo (Nómadas. Critical Journal of Social and Juridical Science, 2012)
Jean-Luc Nancy travels through the body as a Summa, as a corpus, it subtracts the bio-teleological horizon of the body for delivery to the event horizon, which means stop thinking about a body organized on the basis of a purpose separate from each other thereof. Nancy develops a philosophy of the body which reverses the generally accepted interpretation around the place (subordinate) of the body in the constitution of the modern subject. Hence, Nancy insists that "we have a body but we are one body." Thus the new ontological and epistemological status of the body not only make new forms of subjectivity, but also a "new flesh". So at the boundaries between natural and artificial raises the possibility of thinking in a fragmented body, a body whose organs have been emancipated, as Deleuze and Guattari called the Body Without Organs. As will the knowledge of the entire body and is never absolute, but modal split, and the best form of speech acts such knowledge is of a Corpus precisely mapping, an inventory of areas of the body that provides a set of approaches, revealing what Nancy called himself "body signs". Thus we are interested in Corpus is not all organic but detached parts and possible, in multiple relationships. In parallel, examine the post-humanist thought, developed by Sloterdijk, their philosophical sources and technical means, then, from there to address the problem of otherness, the reconfiguration of subjectivity and ontology of the body such as is proposed by Jean-Luc Nancy. This will review the phenomenon of anti-technology hysteria, the metaphors and eschatology of the disease, deepening the experience of a transplant recipient to finish discussing the ethical implications of this sort of ontology of the body that begins to take shape, a modal ontology - if you will-because the body is related more positions, tensions, and weights, with essences or substances